Kualitas Daftar Pemilih Tetap pada Pemilihan Umum Serentak Tahun 2019 di Komisi Pemilihan Umum Kabupaten Humbang Hasundutan - Evlin Helena Manalu; Hendra Harahap; Hatta Ridho (PERSPEKTIF, 2022)
What you want to know in this study is how the quality of voter lists remains in the 2019 Simultaneous Elections. In addition, what are the factors that become obstacles in updating voter data and how efforts are made in overcoming these obstacles. This research method is qualitatively descriptive, by presenting the facts found comprehensively through in-depth analysis. While data analysis techniques consist of data reduction, data presentation and conclusion withdrawal. The results of the research obtained, the system of updating the voter list in the Humbang Hasundutan KPU is not yet at the maximum point, because in the KPU of Humbang Hasundutan Regency there are still found a number of 4,418 voters who entered into special voters or who are not registered in the DPT, a total of 949 elements of NKK data are empty, a total of 66 elements of NIK data are empty and there are double voters as many as 380 voters. The accuracy of other elements of voter data, which cannot be ascertained the truth as well as the lack of oversight of the performance of the adhoc body.